Didactics of Arabic Language Activities in the New Reform Curricula for the Primary Education Stage - messeguem, hamlaoui (El Omda in Linguistics and Discourse Analysis, 2023)
Ministry of National Education, which made it attach great importance to the process of evaluating the performance of learners, especially in the first phase, due to the fact that it is an episodic competence. Therefore, the societal bet on reforming the education system is an objective and legitimate bet. Talking about reforming the education system in Algeria cannot stop at its quantitative dimensions, but rather it must go beyond it to betting on qualit